Increased carotid intima–media thickening and antioxidized low-density lipoprotein in an anti-Ro60 SLE autoantibody subset - Kurien, Biji T.; Fesmire, James; Nath, Swapan K.; Scofield, R. Hal (Frontiers in Lupus, 2023)
Objective: Premature atherosclerosis is associated with systemic lupus erythematosus (SLE). We previously showed an association of anti-Ro60/La/Ro52 to anti-oxidized LDL in SLE. Here, we hypothesized that carotid intima media thickening (CIMT) will be associated with anti-oxidized LDL (anti-oxLDL)/anti-lipoprotein lipase (ALPL) in a specific SLE autoantibody sub-set (anti-Ro60 positive, anti-RNP positive, anti-SmRNP positive, or extractable nuclear antigen antibody negative). Methods: We carried out a case-control study (one time-point testing) of CIMT, ALPL, anti-oxLDL, anti-low density lipoprotein (ALDL) and anti-LDL in 114 SLE and 117 age/sex matched controls. Total cholesterol, LDL, HDL, triglycerides, and HDL-Trig were also measured. Student's t test was used for statistical analysis. Results: Interestingly, CIMT was highest in SLE subset with anti-Ro60 (23/114). CIMT and anti-oxLDL were statistically significantly elevated in the anti-Ro60 SLE subset (1.3±1.66, p<0.01; 0.26±0.16, p<0.002 respectively) compared to controls (0.54±1.26; 0.165±0.13 respectively), but not anti-LPL/anti-LDL. CIMT was significantly elevated (0.9±1.71; p< 0.05) in the SLE subset without anti-extractable nuclear antigen (ENA) (63/114) compared to controls. Other antibodies in this subset were not statistically different compared to other SLE subsets or controls. Only anti-oxLDL was significantly elevated (0.29 ±0.27; p<0.005) in SLE subset with anti-RNP (14/114) compared to controls, while none were elevated in anti-SmRNP subset (6/114). We did not find significant differences in lipids between various SLE subsets. This is a provisional file, not the final typeset article Conclusion: CIMT segregates in anti-Ro and ENA negative groups either with or without anti-oxLDL. It will be clinically important if cardiovascular events are augmented in SLE anti-Ro subset having elevated anti-oxidized LDL antibodies.